O conflito no exercício gerencial do enfermeiro no contexto hospitalar - Guerra, Soeli Teresinha (2008)
This research is a qualitative approach investigation that has the aim of studying the conflict in nurse s management practice in hospital context. Its objective is to analyze the conception nurses have of conflict, to infer the strategies used to solve it and to interpret the phenomenon from the variables it assumes in management ambit. The theoretical references are based on the concepts of habitus and Bourdieu s field and on the disciplines of Nursing and Management. For the data collection, a semistructured interview was used, according to Resolution 196/96. Thirteen nurses, hospital managers of hospitals with more then fifty beds, were the informants of this research. In order to interpret the results, one made use of the technique of content analysis (Minayo, 2007), from which emerged five categories: 1) the manager nurses and their practice; 2) the manager nurses perception and the conflict; 3) manager nurses and their sentences; 4) in presence of conflict, to combat it strictly is needed; 5) the conflict in every day fighting camp. Among the evidences, one highlight: 11 from the 13 nurses are in management function most of 80% of their time as graduated and express they have no Idea about the role of a manager before assuming this function. The whole of them understands that conflicts are inherent to organization and the nurse has to acquaint and interact with it. They reveal that inside conflicts are the most impacting to the managers. One concludes that: it is necessary to understand the origin of conflicts; factors which favor their installation and to recognize the importance to approach them in an interdisciplinary way.